Congenital Heart Defects in Patients with Deletions Upstream of SOX9. Issue 12 (18th October 2013) - Sanchez‐Castro, Marta; Gordon, Christopher T.; Petit, Florence; Nord, Alex S.; Callier, Patrick; Andrieux, Joris; Guérin, Patrice; Pichon, Olivier; David, Albert; Abadie, Véronique; Bonnet, Damien; Visel, Axel; et al.
<x xml:space="preserve">Abstract</x> We report two unrelated families including patients with isolated Pierre Robin Sequence (PRS), isolated congenital heart defect (CHD), or both anomalies. The affected patients carried a similar ~1Mb deletion upstream of SOX9. CHIP‐Seq analysis from mouse cardiac tissue for H3k27ac led us to identify several putative cardiac enhancers within the deleted region. One of these elements interacts with Nkx2.5 and Gata4. These data suggest that disruption of cardiac enhancers located upstream of SOX9 may be responsible for CHDs in humans. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>